KIAI AS AL-QUDWAH AL-KHASANAH: THE ROLE OF KIAI IN SHAPING RELIGIOUS CULTURE IN ISLAMIC EDUCATION INSTITUTION - Ihsan Ihsan; A. Umar (UIN Raden Mas Said Surakarta, 2020)
This study aims to describe the role of kyai in creating the religious culture of the santri. How the socialization patterns that exist in an educational institution especially pesantren (Islamic boarding school) can shape the religious culture of the santri, is the main concern of this study. Madrasah Qudsiyyah, one of the Islamic education institutions based on pesantren in Kudus Regency, Central Java, is the object of this study. With a qualitative approach, the data were collected through participant observation and in-depth interviews. They were then analyzed using the theoretical framework of the sociology of knowledge of Peter L. Berger and Thomas Luckman. The results of this study revealed that kyai (including ustadz) has a central role in shaping the character and religious culture of the santri. Kyai, apart from being an educator, also acts as a guide, uswah hasanah, and guide of the santri. With this role, kyai becomes a kind of role model for santri in terms of the spiritual, moral, intellectual, and social life. From a long time daily interaction process between kyai and santri in the pesantren, finally it becomes habitus in shaping the mindset, character, and religious culture of the santri.